PENGARUH TATA KELOLA PERUSAHAAN YANG BAIK TERHADAP PENGHINDARAN PAJAK (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia pada tahun 2015-2018) - Ayu Anggreni Siregar; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2020)
The purpose of this research is to obtain an empirical evidence about the effect of good corporate governance on tax avoidance which becomes a proxy of current Effective Tax Rate. The independent variables are executive compensation, executive character, company size, institutional ownership, boards of independent commisioners’ proportion, audit committee and audit quality. The dependent variable is Tax avoidance. The hypothesis testing used multiple regression analysis method with secondary data obtained by judgment sampling method . The samples of this study were 142 data from manufacturing companies listed in Indonesian Stock Exchange and published annual report period 2015 – 2018. The result of this study show that executive compensation, boards of independent commisioners’ proportion , audit committee has a positive effect on tax avoidance in partial but the executive compensation, executive character, company size, institutional ownership, boards of independent commisioners’ proportion, audit committee and audit quality have simultaneous effect to define tax avoidance.